A review of focused ion beam sputtering - Ali, Mohammad Yeakub; Hung, Wayne N.P.; Fu, Yongqi (Springer, 2010)
This paper reviews the applications of focused ion beam (FIB) sputtering for micro/nano fabrication. Basic principles of FIB were briefly discussed, and then empirical and fundamental models for sputtering yield, material removal rate, and surface roughness were presented and compared. The empirical models were more useful for application compared to fundamental models. Fabrication of various micro and nano structures was discussed. Trimmed atomic force microscope (AFM) tips were tested in measurement and imaging of high aspect ratio nanopillars where higher accuracy and clarity were observed. Micromilling tool fabricated using FIB sputtering was used to machine microchannels. Slicing and dwell time control approaches on FIB sputtering were presented for the fabrication of three dimensional microcavities. The first approach is preferred for practical applications. The maximum aspect ratio of 13:1 of the microstructures was achieved. The minimum size of the nanopore was in the range of 2-10 μm. Cavities of microgear of 70 μm outside diameter were sputtered with submicrometer accuracy and 2-5 nm average surface roughness. The microcavities were then filled with polymer in a subsequent micromodling process. The replicated microcomponents were inspected with scanning electron microscope where faithful duplication of accuracy and surface texture of the cavity was observed.